Law and Charity Walter Benjamin, Leo Strauss, Georg Simmel, Franz Baermann Steiner - M. Mack (Law Text Culture, 2000)
The concept of law and the associated figure of Moses have recently received much attention: last year alone two books about Moses were published.1 This recent interest bespeaks the necessity to reflect upon law for informed debates about theology in its relation to communal issues.2 Gillian Rose often warned against a perception of Judaism as 'pure' ethics without strong relations to both theology and politics.3 Jewish law is theological and political such that it cannot be separated form coercion as well as from love or charity. Its coercion, however, takes care of the specific of the singular: law as charity does not lord over the world, but asks to be questioned from different perspectives, asks to be applied in new forms from context to context.4 Law as charity aims to preserve the life of specific individuals, or groups of individuals: it protects persons rather than things.5 Rather than being like Roman law, identified with dominum (see Milbank 1990: 12), Jewish law is related to the actions and anxieties of specific people in specific circumstances, making use of coercion not for the sake of the interest of property but with the concern of keeping life as undamaged as possible.